Accuracy of 2-Phase Parathyroid CT for the Preoperative Localization of Parathyroid Adenomas in Primary Hyperparathyroidism - Griffith, B.; Chaudhary, H.; Mahmood, G.; Carlin, A.M.; Peterson, E.; Singer, M.; Patel, S.C. (American Journal of Neuroradiology, 2015)
BACKGROUND AND PURPOSE: Minimally invasive parathyroidectomy requires accurate preoperative localization of suspected adenomas, and multiphase CT allows adenoma characterization while providing detailed anatomic information. The purpose of this study was to assess the feasibility of a protocol using only arterial and venous phases to localize pathologic glands in patients with primary hyperparathyroidism.MATERIALS AND METHODS: We identified 278 patients with primary hyperparathyroidism who had undergone 2-phase CT with surgical cure. All scans were read prospectively by board-certified neuroradiologists. A neuroradiology fellow retrospectively reviewed images and reports and classified suspected adenomas on the basis of anatomic location. Accuracy was determined by comparing imaging results with surgical findings. The ability of 2-phase CT to localize adenomas to 1 of 4 neck quadrants and lateralize them to the correct side was assessed. Accuracy of identifying multigland disease was also evaluated.RESULTS: In patients with single-gland disease, the sensitivity and specificity of 2-phase CT to correctly localize the quadrant were 55.4% and 85.9%, respectively. The sensitivity and specificity of correct lateralization were 78.8% and 67.8%, respectively. The sensitivity and specificity to identify multigland disease were 22.9% and 79.5%, respectively.CONCLUSIONS: While the 2-phase CT protocol in this study demonstrates lower accuracy compared with reports of other techniques, its lower radiation compared with 3- and 4-phase techniques may make it a feasible alternative for preoperative parathyroid localization. Further prospective studies are needed to identify patients for whom this technique is most suitable.